Pemaknaan Toleransi Perspektif Fakhr Ar-Rāzī - Mardina, Dini; Saputra, Edomi (Jurnal Kajian dan Pengembangan Umat, 2023)
Religious tolerance from the past until now is still a central issue. It's easy to say but difficult to do. From year to year there are those who try to disrupt tolerance between religious communities. Uniquely, religious issues are quite sensitive so they are prone to sparking conflict, especially in a pluralistic environment. Religious issues can even easily trigger endless wars. To overcome this problem, there is a need for a tolerant attitude between adherents of one religion and another. Research on religious tolerance has been carried out by many previous researchers. But no one has discussed specifically Fakhr ar-Razi's interpretation of verses in the Koran that relate to tolerance. Such as Qs al-Baqarah [2]: 62, 139-141, 256, al-Maidah [5]: 5, and al-Kafirun [109]: 1-6. The common thread between previous research and that of the author is that they emphasize the importance of inter-religious tolerance to be realized. The main source in this research is at-Tafsīr al-Kabīr by Fakhr ar-Rāzī. Meanwhile, the research method that the author uses is a qualitative method. Language analysis approach. The theory used in this research is the semiological theory formulated by Roland Barthes. As a result, in general Fakhr ar-Razi interpreted the verses of the Koran tolerantly. From this research it can be concluded that Fakhr ar-Razi interpreted Qs al-Baqarah [2]: 62, 139-141, 256, al-Maidah [5]: 5 tolerantly. But when interpreting al-Kafirun [109]: 1-6 Fakhr ar-Razi seems less tolerant.